Entropically Favoured Assembly of Pyrazine‐Based Helical Fibers into Superstructures: Achiral/ Chiral Guest‐Induced Chirality Transformation. (25th September 2019) - Sharma, Sonia; Kataria, Meenal; Kumar, Manoj; Bhalla, Vandana
Abstract: The development of synthetic helical structures undergoing stimuli‐responsive chirality transformations is important for an understanding of the role of chirality in natural systems. However, controlling supramolecular chirality in entropically driven assemblies in aqueous media is challenging. To develop stimuli‐responsive assemblies, we designed and synthesized pyrazine derivatives with l ‐alanine groups as chiral building blocks. These systems undergo self‐assembly in aqueous media to generate helical fibers and the embedded alanine groups transfer their chirality to the assembled structures. Furthermore, these helical fibers undergo a Ni 2+ ‐induced chirality transformation. The study demonstrates the role of intermolecular hydrogen bonding, π–π stacking, and the hydrophobic effect in the Ni 2+ ‐mediated transition of helical fibers to supercoiled helical ensembles which mimic the formation of superstructures in biopolymers. Abstract : Helixbildung : Ein Pyrazinderivat vollzieht eine Helixtransformation in wässrigen Medien, wobei l ‐Alanin die Chiralität kontrolliert. Die Erzeugung spiralförmiger Fasern in wässrigen Medien, der Übergang von der Helix zur aufgerollten Superhelix in Anwesenheit achiraler Gäste (Ni 2+ ‐Ionen) sowie der Übergang von der Supercoil‐Helix zur Superhelix in Anwesenheit chiraler Gäste (d /l ‐Histidin) sind entropisch getriebene Prozesse.